Mastering the game: Understanding the performance psychology component of the PGMOL key performance characteristics model of elite match officiating in association football - Dougan, K.; Russell, P. (BASES Conference 2024, 2024)
Key Performance Characteristics (KPC) are specific attributes and skills essential for achieving high standards and consistent perfor mance in association football match officials (referees and assis tant referees). The Professional Game Match Officials Limited (PGMOL) KPC model is a theoretical framework with nine KPCs, developed by an expert panel of active and former elite match officials, PGMOL coaches and support staff, and English Premier League (EPL) academy coaches. Ethical approval for this review was granted, ensuring adherence to all ethical guidelines and standards. In elite match officiating, KPCs are the cornerstone of holistic performance, development, and assessment. The PGMOL formulated nine KPCs including Developmental Mindset, Leadership, Interpersonal Skills, Match Day Communication, Football Insights, Resilience, Lifestyle Management, and Physical Attributes. Elite match officiating in competitive matches demands exceptional psychological and performance capabilities. MacMahon and Plessner (2008) (MacMahon and Plessner, 2008, International Journal of Sports Science & Coaching, 3, 141-160) highlight the importance of performance metrics in maintaining fairness and integrity in competitive environments. This study explores the significance of KPCs in the context of elite match officiating, focusing on the four KPCs rooted in performance psychology: Leadership, Developmental Mindset, Interpersonal Skills, and Resilience. These psychological characteristics are grounded in Bandura`s Social Cognitive Theory, which hypothe sises that personal factors, behaviour, and environmental influ ences interact to contribute to individual performance (Bandura, 1986, Social foundations of thought and action: A social cognitive theory. Englewood Cliffs). Understanding these KPCs is vital as they help match officials manage the pressures and challenges inherent in their roles. For instance, resilience enables match officials to recover from setbacks, a developmental mindset fosters continuous improvement, leadership skills facilitate effective man agement of on-field dynamics, and strong interpersonal skills enhance communication with players and coaches. By system atically analysing these KPCs, this framework provides a comprehensive structure for developing targeted training pro grammes enhancing the performance of elite association football match officials. By strengthening these KPCs, match officials can experience a comprehensive approach to their development. This review provides a foundation for future research on the impact of KPCs on elite match official holistic development. The implemen tation of psychological support systems within match officials` development programmes aims to optimise the performance and well-being of elite match officials. This research highlights the critical role of psychological preparedness in achieving excel lence in officiating, advocating for a thorough and all-embracing approach to match officials` development that integrates technical skills, psychological and physical aspects of performance.